Model Kolaborasi Global di Kelas SD: Studi Kasus Virtual Exchange Tahun 2025 - Putri, Rahmawati; Maulana, Ahmad Fikri; Pramudita, Diah Lestari (Gema Cendekia Institute, 2026)
Globalization and digital technology development have opened new opportunities in elementary education through global collaboration based on virtual exchange. This study explores the implementation of a global collaboration model in elementary school classrooms through virtual exchange programs in 2025. To analyze the effectiveness of the virtual exchange model in developing global competencies, collaborative skills, and intercultural awareness among elementary school students. This study employed a qualitative case study approach involving 120 fifth-grade students from three countries (Indonesia, Spain, and Australia) who participated in a 12-week virtual exchange program. Data were collected through online learning observations, in-depth interviews with teachers and students, digital artifact analysis, and student reflections. Findings indicate that virtual exchange significantly enhanced students' cultural awareness, cross-cultural communication skills, and global critical thinking abilities. Students demonstrated increased learning motivation and collaborative capabilities in multicultural contexts. The virtual exchange model proves effective as an innovative pedagogical strategy for developing global citizenship competencies at the elementary education level, with important implications for curriculum development and 21st-century learning practices.